Antibiotic exposure and risk of overweight/obesity in children: a biomonitoring-based study from eastern Jiangsu, China - Sun, Huamin; Huang, Jianping; Zhou, Yijing; Guo, Xinying; Jiao, Man; Zhu, Xingchen; Tan, Weiwei; Zhang, Weibing (Frontiers in Public Health, 2024)
ObjectiveTo describe antibiotic exposure in children and explore its association with overweight/obesity.MethodsIn June 2022, 328 kindergarten and primary school children were selected from Nantong city in Jiangsu Province. Questionnaires were distributed, and morning urine samples were obtained. Total urinary concentrations of 41 antibiotics were measured using ultra-performance liquid chromatography and tandem mass spectrometry. The rates of antibiotic exposure were expressed as percentages (%), specific percentiles (P95 and P99), and the maximum values were used to describe the concentration of antibiotics. The association between urinary antibiotic creatinine-adjusted and overweight/obesity was analyzed using logistic regression.ResultsA total of 328 children were initially recruited, of which 295 aged 3–8 years met the inclusion criteria and were finally included in the study. The biomonitoring results revealed that 35 antibiotics were detected, with a total detection frequency of 98.31%. Among the included children, 24.75% were classified as overweight/obesity. Multinomial logistic regression analyses revealed significant associations between overweight/obese and exposure to veterinary antibiotics (VAs) and preferred veterinary antibiotics (PVAs). After adjusting for various overweight/obesity-relevant variables, higher exposure to sulfamethoxazole [OR = 2.35, 95% confidence interval (CI):1.17–4.70], norfloxacin (OR = 2.66, 95% CI: 1.01–7.08), and fluoroquinolones (OR = 1.97, 95% CI: 1.02–3.78) were significantly associated with overweight/obesity (p < 0.05). In addition, after stratification by sex and adjustment for confounding variables, sex-specific differences were observed in the association between antibiotic exposure and overweight/obesity. Notably, these associations were predominantly observed among boys.ConclusionChildren were extensively exposed to antibiotics. Exposure to certain types of veterinary antibiotics and preferred veterinary antibiotic exposure, mainly through food or drinking water, are associated with an increased risk of overweight/obesity in children.